Determinants of psychological well-being in axial spondyloarthritis: an analysis based on linked claims and patient-reported survey data. Issue 7 (10th March 2018) - Redeker, Imke; Hoffmann, Falk; Callhoff, Johanna; Haibel, Hildrun; Sieper, Joachim; Zink, Angela; Poddubnyy, Denis
Abstract : Objectives: The aim of this study was to assess the psychological well-being and to analyse factors associated with depressive symptoms in axial spondyloarthritis (axSpA). Methods: A stratified random sample of subjects with a diagnosis of axSpA (International Classification of Diseases, Tenth Revision, German Modification M45) was drawn from health insurance data in Germany. These persons received a postal questionnaire on disease-related, psychological and lifestyle factors as well as socioeconomic status. Additional information to verify the axSpA diagnosis was also collected. The psychological well-being was assessed by means of the 5-item WHO Well-Being Index (WHO-5), which is considered a screening tool for depression. The following established cut-offs on the WHO-5 were applied: >50: good well-being, no depressive symptoms; 29–50: mild depressive symptoms; ≤28: moderate-to-severe depressive symptoms. Information on comorbidities, drug prescriptions and non-pharmacological treatment was retrieved from claims data and linked to the questionnaire data. Results: A total of 1736 persons with a confirmed axSpA diagnosis were included. Using the cut-offs on the WHO-5, 533 persons (31%) were found to have moderate-to-severe depressive symptoms, 479 (28%) had mild depressive symptoms and 724 (42%) had a good well-being. Multivariable logistic regression revealed that higher disease activity, higher level of functional impairment, lower income, self-reported stress and lack of exercise, and younger age represent factors associated with moderate-to-severe depressive symptoms. Conclusions: The prevalence of depressive symptoms in axSpA subjects is high and associated with disease-related parameters, socioeconomic status and lifestyle factors. These findings highlight the need for the careful evaluation of depressive symptoms as a part of the management strategy for axSpA.